Study on Power Grid Partition and Attack Strategies Based on Complex Networks - Zou, Yanli; Li, Haoqian (Frontiers in Physics, 2022)
Based on the community discovery method in complex network theory, a power grid partition method considering generator nodes and network weightings is proposed. Firstly, the weighted network model of a power system is established, a improved fast-Newman hierarchical algorithm and a weighted modular Q function index are introduced, and the partitioning algorithm process is practically improved combined with the characteristics of the actual power grid. Then, the partition results of several IEEE test systems with the improved algorithm and with the fast Newman algorithm are compared to demonstrate its effectiveness and correctness. Subsequently, on the basis of subnet partition, two kinds of network attack strategies are proposed. The cascading fault survivability of different types of networks under four attack strategies is simulated and analyzed. It is found that the proposed two attack strategies based on subnet partition are better than the two traditional attack strategies.